First Report of Powdery Mildew in Eucalyptus Caused by Erysiphe neolycopersici in China - Zhu, Linhui (Plant disease, 2022)
Eucalyptus is one of the most fast-growing and widely planted hardwood trees in the tropical and subtropical regions (Grattapaglia and Kirst, 2008). In December 2021, powdery mildew diseases were observed on the Eucalyptus urophylla, E. urophylla × E. grandis, E. grandis × E. urophylla, and E. grandis trees growing in the Eucalyptus garden of the Guangxi University campus in Nanning (108°22'E, 22°48'N) of Guangxi Zhuang Autonomous Region, where is the main plantation area for Eucalyptus. The spread of this disease would bring potential challenges on the Eucalyptus plantation management in this region of China. The early symptoms of this disease in Eucalyptus were that the irregular white spots with surface-attached powder was observed on the leaves. At the late stages, this symptom was diffused to the whole leaves and even petioles and stems. It would finally cause significant defoliation, but barely lead to plant death in Eucalyptus. Microscopic observation showed that the mycelium was straight or flexuous, hyaline, thin-walled, septate, branched, and 3-7 μm wide (n = 50; average 4.86 μm). The appressorium was lobed and attached to one end of the mycelium alone, or paired attached to both ends of the mycelium. The conidiophore was straight or flexuous, unbranched, 54-100 × 6-10 μm (n = 40; average 75.47 μm × 8.22 μm). One to 3 conidium were connate on the conidiophores. Foot-cells were straight or flexuous at base, 5-8 μm wide (n = 40; average 6.53 μm). The conidium were ellipsoid or oval, and the size was 38-56 × 12-21 μm (n = 70; average 44.92 μm × 15.69 μm). The lobed or rod-shaped bud tube was produced at the conidium. According to the morphology, the fungus was identified as Erysiphe neolycopersici (Hsiao, et al. 2022). For the molecular characterization of the isolate, the sequences of the internal transcribed spacer (ITS), the 18S and 28S large subunit ribosomal DNA (SSU and LSU) (Scholin et al. 1994 , White et al. 1990), were sequenced and deposited in GenBank (OM422667, OM424285 and ON514159). The phylogenetic analysis showed that the ITS sequence showed 100% identity with sequences of E. neolycopersici (MW082786, MT370492, and JQ972700). The 28S rDNA sequence had the highest identity (99.69%) with that of E. neolycopersici (LC371327, LC371320, and OM368490). The SSU sequence had the highest identity (99.72%) with that of E. neolycopersici (LC516961). The pathogenicity test of the fungus was repeated thrice following the Koch's postulates. The diseased leaves were gently rubbed against 3 to 4 healthy mature leaves of more than five E. grandis seedlings (two-month-old). The inoculated and control plants were then cultured in the greenhouse (25 ℃, 16-h light/8-h dark and 70% humidity). Similar disease symptoms were observed on the inoculated leaves, but not on the control leaves seven days after inoculation. The isolates from three independent experiments were morphologically and genetically identical with the original isolate. As far as we know, this study is the first report of powdery mildew disease in Eucalyptus caused by E. neolycopersici in China